Revolutionaries of India in Soviet Russia - "Persits, M. A." (Moscow, 1973)
The October Revolution and the east is a subject which, for all the abundance of studies about it, is still far from exhausted. With more research findings available and more evidence discovered, it becomes clear that the impact of the October Revolution on Asia has been greater and deeper than it was first believed to have been. This is the conclusion one arrives at when reading a book that brings out some hitherto unknown aspects of the influence the Great October Socialist Revolution had on the struggle of imperialist -oppressed peoples.
Keywords: Revolutionist-Soviet Union